Investigation of the stability of dairy systems, rehydrated using cavitation disintegration - D. A. Salmanova; A. A. Bratsikhin; I. A. Evdokimov; A. A. Blinova (Современная наука и инновации)
One of the main requirements for a rehydrated dairy system is stability throughout the entire shelf life. In samples of dairy systems «skimmed milk powder – demineralized whey powder» rehydrated using cavitation disintegration, the values of the zeta potential of dispersed phase particles, as well as the average hydrodynamic radius of casein micelles were studied in order to study the effect of ultrasound treatment modes, as well as the percentage of replacement of skimmed milk powder with dry demineralized whey in solution and their influence on the stability of the resulting system.